2015
DOI: 10.1167/15.15.19
|View full text |Cite
|
Sign up to set email alerts
|

Role of form information in motion pooling and segmentation

Abstract: Traditional theories of visual perception have focused on either form or motion processing, implying a functional separation. However, increasing evidence indicates that these features interact at early stages of visual processing. The current study examined a well-known form-motion interaction, where a shape translates along a circular path behind opaque apertures, giving the impression of either independently translating lines (segmentation) or a globally coherent, translating shape. The purpose was to syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…A moving background may change the apparent size, shape and position of briefly flashed objects (Anstis & Cavanagh, 2017). Movement speed can affect perceptual grouping and global shape (Anstis, 2005), and, in a now well-studied occluded-aperture stimulus, stimulus configuration can affect whether four bars appear to be a single object moving coherently in one direction or as four separate objects moving independently (Lorenceau & Alais, 2001; Lorenceau & Shiffrar, 1992; McDermott & Adelson, 2004; Shiffrar & Lorenceau, 1996; Tang, Dickinson, Visser, Edwards, & Badcock, 2015). Rotational motion in particular has been found to distort the perceived shape and size of objects (Anstis, Sturzel, & Spillmann, 1999; Caplovitz & Tse, 2006; McDermott & Adelson, 2004; Meyer & Dougherty, 1990; Shiffrar & Pavel, 1991; Stanley, 1968; Weiss & Adelson, 2000).…”
Section: Hallmarks Of Object-related Representations In Dorsal Cortexmentioning
confidence: 99%
“…A moving background may change the apparent size, shape and position of briefly flashed objects (Anstis & Cavanagh, 2017). Movement speed can affect perceptual grouping and global shape (Anstis, 2005), and, in a now well-studied occluded-aperture stimulus, stimulus configuration can affect whether four bars appear to be a single object moving coherently in one direction or as four separate objects moving independently (Lorenceau & Alais, 2001; Lorenceau & Shiffrar, 1992; McDermott & Adelson, 2004; Shiffrar & Lorenceau, 1996; Tang, Dickinson, Visser, Edwards, & Badcock, 2015). Rotational motion in particular has been found to distort the perceived shape and size of objects (Anstis, Sturzel, & Spillmann, 1999; Caplovitz & Tse, 2006; McDermott & Adelson, 2004; Meyer & Dougherty, 1990; Shiffrar & Pavel, 1991; Stanley, 1968; Weiss & Adelson, 2000).…”
Section: Hallmarks Of Object-related Representations In Dorsal Cortexmentioning
confidence: 99%
“…The authors modulated the contrast of each component and showed that by manipulating whether modulation occurred asynchronously or synchronously across the components, perception could be biased towards either the local or global solution, respectively. However, their stimulus contained form information, i.e., an unambiguous diamond shape, which has been shown to augment temporal synchrony-based grouping (Leonards, Singer, & Fahle, 1996;Tang, Dickinson, Visser, Edwards, & Badcock, 2015;Usher & Donnelly, 1998) in excess of the probability summation of the two properties (Lee & Blake, 2001). Similarly, Blake (1999, 2001) and Morgan and Castet (2002) demonstrated the capacity of temporal synchrony to drive segmentation using static stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The increased in accuracy of similar targets reported in Experiment 1, along with the attractive biasing of target orientations are reminiscent of serial dependency effects 28,29 and opposite to tilt-aftereffects where adaptation to an orientation causes repulsion for similar orientations and decreased accuracy 71,72 . The repulsive tilt aftereffect is well predicted by simple information channel models 72,73 , which are consistent with the neurophysiological evidence that visual neurons exhibit orientation-selective adaptation with the most similar orientations causing the greatest adaptation 74,75 . Using the same simple model architecture, but having the adapter increase the sensitivity of the affected channels allows for attractive aftereffects which are consistent with serial dependency 72 .…”
Section: Discussionmentioning
confidence: 77%